Analysis of the impeller's tip clearance size on the operating characteristics of the underwater vehicle with a new high-speed water jet propulsion pump. (15th September 2021) - Lu, Yeming; Wang, Xiaofang; Liu, Haoran; Zhou, Fangming; Tang, Tao; Lai, Xide
Abstract: To make up for the lack of study on high-speed water jet propulsion pump tip clearances, a newly developed water jet pump system close to the critical specific speed nsc has been investigated. Based on the body of the underwater vehicle and the non-uniform flow, the pump system with different tip clearance sizes (0.1, 0.2, 0.4, 0.8 mm) is evaluated and validated via numerical simulations. Preliminary steady simulating results demonstrate that increasing the tip clearance size can reduce the overall performance of the head, the efficiency, pump thrust, and the consuming power. Following further unsteady simulations, we reveal the unsteady dynamic performance induced by the tip clearances, related to the similar distribution characteristics of the pressure intensities and the pressure pulsations around the underwater vehicle. Furthermore, the pressure intensity and pressure pulsations in the pump increase with the tip clearance. Quantitative and comparative analysis of the distribution characteristics indicates that the blade loading and scrapping effect of the shroud are key factors influencing the leakage flow. At last, the leakage flow's dynamic distributing law under different tip clearances have been clarified. Highlights: 1) Considering the influence of the underwater vehicle's body and the non-uniform flow, the operating characteristics of the underwater vehicle with high-speed water jet propulsion pump have been investigated. 2) The key steady and unsteady dynamic performances of the underwater vehicle controlled by the tip clearances have been illustrated. 3) The mechanism of the leakage flow and the influence factors have been quantitatively analyzed. 4) The dynamic distributing laws for the leakage flow under different tip clearances have been clarified.